CaMKII-mediated Beclin 1 phosphorylation regulates autophagy that promotes degradation of Id and neuroblastoma cell differentiation. Issue 1 (December 2017) - Li, Xuan; Wu, Xiao-Qi; Deng, Rong; Li, Dan-Dan; Tang, Jun; Chen, Wen-Dan; Chen, Jing-Hong; Ji, Jiao; Jiao, Lin; Jiang, Shan; Yang, Fen; Feng, Gong-Kan; et al.
Abstract Autophagy is a degradative pathway that delivers cellular components to the lysosome for degradation. The role of autophagy in cell differentiation is poorly understood. Here we show that CaMKII can directly phosphorylate Beclin 1 at Ser90 to promote K63-linked ubiquitination of Beclin 1 and activation of autophagy. Meanwhile, CaMKII can also promote K63-linked ubiquitination of inhibitor of differentiation 1/2 (Id-1/2) by catalyzing phosphorylation of Id proteins and recruiting TRAF-6. Ubiquitinated Id-1/Id-2 can then bind to p62 and be transported to autolysosomes for degradation. Id degradation promotes the differentiation of neuroblastoma cells and reduces the proportion of stem-like cells. Our study proposes a mechanism by which autophagic degradation of Id proteins can regulate cell differentiation. This suggests that targeting of CaMKII and the regulation of autophagic degradation of Id may be an effective therapeutic strategy to induce cell differentiation in neuroblastoma. Neuroblastoma cell differentiation is regulated by Id proteins. Here, the authors show that CaMKII-mediated phosphorylation of Beclin 1 can activate K63-linked ubiquitination and autophagic degradation of Id proteins uncovering a role for autophagy in cell differentiation.